Long noncoding RNA MALAT1 controls cell cycle progression by regulating the expression of oncogenic transcription factor B-MYB. - Vidisha Tripathi; Zhen Shen; Arindam Chakraborty; Sumanprava Giri; Susan M Freier; Xiaolin Wu; Yongqing Zhang; Myriam Gorospe; Supriya G Prasanth; Ashish Lal; Kannanganattu V Prasanth (PLoS Genetics, 2013)
The long noncoding MALAT1 RNA is upregulated in cancer tissues and its elevated expression is associated with hyper-proliferation, but the underlying mechanism is poorly understood. We demonstrate that MALAT1 levels are regulated during normal cell cycle progression. Genome-wide transcriptome analyses in normal human diploid fibroblasts reveal that MALAT1 modulates the expression of cell cycle genes and is required for G1/S and mitotic progression. Depletion of MALAT1 leads to activation of p53 and its target genes. The cell cycle defects observed in MALAT1-depleted cells are sensitive to p53 levels, indicating that p53 is a major downstream mediator of MALAT1 activity. Furthermore, MALAT1-depleted cells display reduced expression of B-MYB (Mybl2), an oncogenic transcription factor involved in G2/M progression, due to altered binding of splicing factors on B-MYB pre-mRNA and aberrant alternative splicing. In human cells, MALAT1 promotes cellular proliferation by modulating the expression and/or pre-mRNA processing of cell cycle-regulated transcription factors. These findings provide mechanistic insights on the role of MALAT1 in regulating cellular proliferation.